Pharmaceutical consultation to detect drug interactions in patients treated with oral chemotherapies: A descriptive cross‐sectional study. (19th December 2020) - Lachuer, Célia; Perrin, Germain; Chastel, Aymeric; Aboudagga, Hail; Thibault, Constance; Delanoy, Nicolas; Caudron, Eric; Sabatier, Brigitte
Abstract: Objective: The development of oral chemotherapy (OC) has led to the recent establishment of multidisciplinary programmes involving pharmacists. We evaluated the utility of our local programme for detecting potential interactions with OCs, particularly drug–drug interactions (DDIs) and herbal–drug interactions (HDIs). Methods: We performed a single‐centre retrospective descriptive study of patients on OC attending a pharmaceutical consultation (PC) during a seven‐month period. These consultations included the use of various complementary tools/databases to search for interactions. Results: We analysed 308 treatments taken by 42 consecutive patients. Fifty‐four potential interactions with OCs were detected in 26% ( n  = 79) of the treatments taken by patients: 46 DDIs (32 minor, 12 major, 2 contraindicated) and eight HDIs. Five interventions associated with interactions were suggested by pharmacists during the consultations (4 were taken into account by oncologists). The total mean time spent on each PC for an individual patient was 80 minutes (36 minutes of preparation, 44 minutes with the patient). Conclusion: This pilot study highlights the importance of studying interactions in such patients, and of the expertise of pharmacists for detecting interactions, which were found in more than one in four treatment lines. The further development of such activities, which already take up considerable amounts of time, is therefore warranted.